Educators' Life Skills in the Era of Smart Society 5.0 - Saputra, Aan Endaniyar; Mirsafa, Ludya (Lembaga Penelitian dan Pendidikan Mandala, 2023)
AbstractEducators as one of the components of national education that have an important role in an educational institution. Seknun stated that